A new approach to vein and arteriovenous fistula dilation. (2nd March 2020) - Desai, Sanjay C; Inston, Nicholas; Mallios, Alexandros
Abstract : Dr Sanjai Desai, Dr Nicholas Inston, and Dr Alexandros Mallios provide an update on a new method to enhance vascular access outcomes for dialysis patients. While arteriovenous fistulas (AVFs) are the 'gold standard' for haemodialysis access, the path to a functional AVF is steep, and far too many fail before they can be used for dialysis. Fist Assist, a lightweight, wearable medical device, provides gentle, intermittent pneumatic compression that can safely and effectively help veins to enlarge before, and after, AVF surgery. This article covers the risks of AVF failure, early research with Fist Assist on dilation, a concise cost analysis, and the potential for such a device to improve outcomes for both percutaneous and standard AVFs. Fist Assist is expected to launch in Europe in March 2020.